Underlying Factors Driving Fiscal Effort in Emerging Market Economies - Baig, Taimur (IMF Working Papers; Working Paper ;, 2005)
Using a panel dataset of 34 emerging market countries for the period 1990-2002, we examine the roles of various economic, political, and institutional variables in determining fiscal effort, as proxied by the primary surplus. We find that while fiscal effort increases, as expected, with the level of lagged debt, this effect tapers off beyond a certain threshold. We also find an inverse U-shaped relationship between the primary balance and revenue. Fiscal effort rises with positive shocks to oil prices (for oil exporters), when the economy grows above its potential, and in the presence of an IMF-supported program. In contrast, high democratic accountability and strong and impartial bureaucracies help lower market risk and hence lower the relative need for fiscal adjustment. Finally, fiscal effort tends to decline when too many constraints are faced by the executive.